Financial subsidies and tax incentives mechanisms in promoting innovation quality in strategic emerging industries - Liu, Qiuhong; Othman, Rani Diana; Kamarudin, Siti Nurhazwani (International Journal of Accounting, Finance and Business, 2025)
In the context of global economic development, innovation is widely recognized as a crucial driver of economic progress. Currently, the entire globe is undergoing a surge in the digital era and significant scientific advancements, accompanied by a heightened level of global investment in research and development. The Chinese government advocates that innovation should be the primary driving force for development. Enterprises play a crucial role in driving innovation and can effectively facilitate the translation of scientific and technological advancements. The quality of innovation in strategic emerging industries is directly linked to the achievement of broader scientific and technological development objectives. China has consistently provided financial subsidies and tax incentives to foster the growth of innovative quality in strategic developing industries. Extensive studies have been conducted to determine the efficacy of policies in enhancing innovation quality and addressing market failure. Nevertheless, the differences in the studies’ perspectives and inconsistencies in their conclusions, resulting in a lack of united opinion. This study aims to provide a clearer understanding of the practicality and importance of improving innovation quality in strategic emerging industries. It does so by examining the development and mechanism of financial subsidies and tax incentives that are used to promote innovation in these industries.